Kemampuan Kognitif Momentum dan Impuls ditinjau dari Hasil Belajar Peserta Didik dengan Model Inkuiri Terbimbing: Indonesia - Maidya Anugerah; Muhammad Zuhdi; Muh Makhrus (Prodi Fisika FKIP Unram, 2022)
The purpose of this study was to determine the students' cognitive abilities after the implementation of the guided inquiry learning model on the material momentum and impulse at MAN 2 Mataram. The type of research used is Research & Development with 4D models. The data collection technique used is students' worksheet on cognitive abilities and instrument test of cognitive abilities. Data during learning activities obtained from the results of the Students Worksheet (LKPD) on cognitive abilities, while the result the increase in the ability of students is obtained from the results of pretest and posttest of students using the N-Gain test. The average result of the pretest The results obtained are 34.42, the average posttest result is 94.76. The average cognitive ability per learner indicator gets N-Gain of 0.63 in the medium category. The highest increase was found in remembering indicator (C1) with an N-Gain of 0.78 in the category high, while the lowest increase was in the category of creating (C6) with an N-Gain of 0.44 in the medium category. Percentage increase in cognitive abilities with high category by 38.10%, the medium category is 61.90% and there is no low category, so the the guided inquiry learning model is effective can be improve the cognitive abilities of students in the material of momentum and impulse. Keywords: Guided Inquiry Learning Model, Cognitive Abilities, Momentum and Impulse.